Pengetahuan Dan Sikap Keluarga Tentang Jamban Sehat Di Desa Gayaman TR 1 RW 2 Mojoanyar Mojokerto - Eka Diah Kartiningrum (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2010)
The health latrine is the room has facilitation to throw human dirty. The increasing of growth residents and the decreasing earning of society get caused by too difficult in latrine problem. There is also factor that causes society doesn’t understand about latrine problem, because there is assumtion all of sanitation problem accord to government’s matter. The aim of this research is to know about realtionship with family attitude about the healthy latrine in RT 1 RW 2 desa Gayaman Mojoanyar of Mojokerto. This research used by correlation design. Population research is all of families RT 1 RW 2 Desa Gayaman Mojoanyar of Mojokerto that amount of 44 “KK”, and research sample is 38 “KK” that are taken by simple random sampling. There are two variables in this research. They are independet variable and dependent variable. The first explain about knowledge of the health “jamban” dan the second explains family attitude to the healthy latrine”. The result of this research anaylized uses chi square examination, where X2 counting > X2 table with α =0.05 where X2 counting=7.56 dan X2 table = 5.591 so Ho refused (H1 accepted) means that there is relationship between knowledge with family attitude for the health “jamban in RT1 RW2 Desa Gayaman of Mojokerto. The good knowledge will effects attitude, so the whole understanding in attitude, knowledge, confidence and emotion are very important in this problem. The conclusion is the most responder has good knowledge dan positive attitude hopely the family keep more health member of their family by keeping their environment and one of the attitude is to clean and keep latrine.